2008
DOI: 10.1371/journal.pone.0001406
|View full text |Cite
|
Sign up to set email alerts
|

Life Depends upon Two Kinds of Water

Abstract: BackgroundMany well-documented biochemical processes lack a molecular mechanism. Examples are: how ATP hydrolysis and an enzyme contrive to perform work, such as active transport; how peptides are formed from amino acids and DNA from nucleotides; how proteases cleave peptide bonds, how bone mineralises; how enzymes distinguish between sodium and potassium; how chirality of biopolymers was established prebiotically.Methodology/Principal FindingsIt is shown that involvement of water in all these processes is man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 31 publications
4
73
0
Order By: Relevance
“…27 The water molecules in these domains are either loosely bonded (low-density) or more tightly bonded (high-density) bonded water molecules. The water in the low-density domains is proposed as having more energy than the water in the high-density domains.…”
Section: Kelea As a Potential Expression Of Chemical Energymentioning
confidence: 99%
“…27 The water molecules in these domains are either loosely bonded (low-density) or more tightly bonded (high-density) bonded water molecules. The water in the low-density domains is proposed as having more energy than the water in the high-density domains.…”
Section: Kelea As a Potential Expression Of Chemical Energymentioning
confidence: 99%
“…The model suggests that liquid water consists of rapidly exchanging high and low density micro-domains, and the equilibrium between these domains can be altered by dissolved solutes [18,55]. This is supported by distinct elution profiles for glucose enantiomers, suggested to involve micro-domain equilibrium shifts, wherein the bioactive enantiomer prefers a less dense aqueous environment and L-glucose favors a more dense water state [55]. Based on this hypothesis, the individual enantiomers are expected to have distinct effects on nucleation independent of solution pH.…”
Section: On Sugar Stereoisomersmentioning
confidence: 99%
“…The additives tested are betaine, ectoine, trehalose, sorbitol, mannitol, glycine, urea, thiourea, and guanidium. With reports of the stereoisomers of mono-and oligo-saccharides in chaotropic and kosmotropic behavior [55], D-and L-forms of sugars are also investigated. The analytical approach involves potentiometric titrations performed by dosing calcium chloride into a solution of an additive dissolved in carbonate buffer.…”
Section: Introductionmentioning
confidence: 99%
“…According to Philippa Wiggins, high density water and low density water has preferential affinities for kosmotropes and chaotropes respectively [23,24]. Wiggins has further suggested that the spontaneous inter-conversion of these two forms of water in microdomains inside cells or enzyme active sites may be what gives life its seemingly boundless 'free energy'.…”
Section: What's the Cell Really Like?mentioning
confidence: 99%